Efficacy and safety of elinzanetant in vasomotor symptoms associated with menopause: A meta-analysis of randomized controlled trials - Sobral, Milene Vitória Sampaio; Rocha, Paula; Rodrigues, Livia Kneipp; Barbosa, Abner Mácola Pacheco [UNESP]; da Rocha, Naila Camila [UNESP]; Peres, Clara de Andrade Pontual; Furtado, Claudio Lucca Lima; da Silva, Danieli Pereira; de Moraes, Marina Ayabe Gomes; Alvarez-Galiana, Veronica (Elsevier, 2025)
Objective: To evaluate the efficacy and safety of elinzanetant compared to placebo in patients experiencing vasomotor symptoms (VMS) associated with menopause. Methods: A systematic search of PubMed, Embase, and Cochrane databases identified randomized clinical trials (RCTs) comparing elinzanetant and placebo in patients with menopause-related VMS. Statistical analyses pooled mean difference (MD) and risk ratio (RR) with 95% confidence intervals (CI) using R Studio 4.3.2. Pre-specified outcomes included frequency and intensity of VMS, quality of life, and sleep disturbance. Results: This meta-analysis included three randomized clinical trials reporting data on 995 patients, with 551 receiving elinzanetant. The mean age ranged from 54.4 to 55.6 years. Elinzanetant significantly reduced VMS frequency (MD −3.09; 95 % CI −4.18 to −2.01; I2 = 0 %) and intensity (MD −0.32; 95 % CI −0.43 to −0.21; I2 = 39 %). Improvements in quality of life were demonstrated by reduced scores on the Menopause-Specific Quality of Life Questionnaire (MD −0.46; 95 % CI −0.63 to −0.30; I2 = 35 %) and better sleep quality measured by the Patient-Reported Outcomes Measurement Information System Sleep Disturbance – Short Form 8b (MD −4.65; 95 % CI −5.56 to −3.73; I2 = 0 %). The incidence of adverse events was similar between groups (RR 1.11; 95 % CI 0.99 to 1.25; I2 = 35 %). Conclusion: Elinzanetant reduces the frequency and intensity of VMS and enhances quality of life and sleep quality in patients with menopause-related symptoms. Its safety profile is comparable to placebo.